2019
DOI: 10.1111/1753-6405.12876
|View full text |Cite
|
Sign up to set email alerts
|

High burden of infectious disease and antibiotic use in early life in Australian Aboriginal communities

Abstract: Objective: To quantify the childhood infectious disease burden and antibiotic use in the Northern Territory’s East Arnhem region through synthesis and analysis of historical data resources. Methods: We combined primary health clinic data originally reported in three separate publications stemming from the East Arnhem Healthy Skin Project (Jan‐01 to Sep‐07). Common statistical techniques were used to explore the prevalence of infectious conditions and the seasonality of infections, and to measure rates of antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
1
17
0
1
Order By: Relevance
“…infections, it has been suggested that the appropriateness of antibiotic prescriptions is higher in remote communities compared to urban areas. [9] There is a significant dearth of data on prescription rates and prescription appropriateness for antibiotic use in rPHC services. With AMR increasing, surveillance is needed in these communities who, with an already high infection prevalence, are at particular risk.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…infections, it has been suggested that the appropriateness of antibiotic prescriptions is higher in remote communities compared to urban areas. [9] There is a significant dearth of data on prescription rates and prescription appropriateness for antibiotic use in rPHC services. With AMR increasing, surveillance is needed in these communities who, with an already high infection prevalence, are at particular risk.…”
Section: Plos Onementioning
confidence: 99%
“…Evidence suggests Australian Aboriginal children are prescribed antibiotics at a higher rate than non-Aboriginal children of the same age. [8,9] This is likely due to increased prevalence of infectious diseases requiring antibiotics, a factor which is further heightened among Aboriginal children living remotely in the NT. [9,10] PHC presentations for impetigo and otitis media (OM) are frequent with 87% of children aged <24 months and 91% aged 6-30 months attending a PHC service for which antibiotics were prescribed in 49% [11] and 48% [12] of cases respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this burden, high frequency appropriate antimicrobial use is required: 95% of children receive at least one antibiotic prescription and 47% receive at least six antibiotic prescriptions by their first birthday . Antimicrobials are also used more often for sore throat treatment to prevent serious complications such as rheumatic heart disease .…”
Section: Heavy Burden Of Infections and Antimicrobial Usementioning
confidence: 99%
“…11 Due to this burden, high frequency appropriate antimicrobial use is required: 95% of children receive at least one antibiotic prescription and 47% receive at least six antibiotic prescriptions by their first birthday. 12 Antimicrobials are also used more often for sore throat treatment to prevent serious complications such as rheumatic heart disease. 4 Other contributors to high rates of antimicrobial use include the absence of senior clinical staff and high staff turnover rates, 13 lack of diagnostic capability, 14 and remoteness (where lack of treatment may precipitate the need for retrieval to a distant hospital).…”
Section: Heavy Burden Of Infections and Antimicrobial Usementioning
confidence: 99%
“…El 45% de los niños indígenas australianos presentan piodermitis y la misma se presenta durante todo el año, debido al hacinamiento y las malas condiciones ambientales en dichas comunidades, en las que coexisten las infecciones estreptocócicas con la (17) escabiosis . El clima cálido y húmedo favorece el desarrollo de piodermitis por la mayor presencia de patógenos en la piel, así como por la aparición de insectos, cuyas picaduras ocasionan prurito, predisponiendo a los traumatismos cutáneos ocasionados por el rascado, lo que favorece la aparición de las enfermedades estreptocócicas, debido a que sirven de puerta de entrada para el S t r e p t o c o c c u s p y o g e n e s e n p e r s o n a s q u e habitualmente no practican normas adecuadas de (18,19) higiene personal .…”
Section: Discussionunclassified